Diagnosis of lymph node tuberculosis using the GeneXpert MTB/RIF in Tunisia. Issue 4 (December 2015) - Ghariani, Asma; Jaouadi, Taha; Smaoui, Selma; Mehiri, Emna; Marouane, Chama; Kammoun, Sana; Essalah, Leila; Driss, Maha; Messadi, Feriele; Slim-Saidi, Leila
Abstract: Introduction: GeneXpert MTB/RIF is a fully-automated diagnostic molecular test which simultaneously detects tuberculosis (TB) and rifampicin (RIF) drug resistance. The purpose of this study is to evaluate the performance of the GeneXpert MTB/RIF test for the detection of Mycobacterium tuberculosis complex (MTBC) in lymph node specimens and to show the place of Mycobacterium bovis as a major cause of TB lymphadenitis. Material and methods: This study was conducted simultaneously in the National Reference Laboratory for Mycobacteria of Ariana and the Central Laboratory of Sfax, from January to December 2013. In total, 174 lymph node specimens were processed simultaneously for Ziehl–Neelsen, auramine and immuno-histochemical staining. Conventional culture on both Lowenstein–Jensen and liquid medium (Bactec MGIT 960 BD system) and the new molecular-based GeneXpert MTB/RIF assay system were performed. Positive cultures were confirmed using molecular identification (Genotype MTBC Hain Lifescience). Results: Among the 174 samples tested, the GeneXpert detected the DNA of MTBC in 134 samples (77%). Standard bacteriological assays, including AFB microscopy and culture, were positive, respectively, in 41 (23.6%) and 79 (45.4%) specimens. M. bovis was isolated in 76% of positive cultures. GeneXpert sensitivity and specificity results were assessed according to smear and culture results, clinical and histological findings. The sensitivity and specificity of the Xpert assay were 87.5% (126/144) and 73.3%, respectively. Conclusion: The implementation of the GeneXpert MTB/RIF assay may dramatically improve the rapid diagnosis of lymph node TB.